Design of a Culinary Information System at Piksi Ganesha Polytechnic Using the Waterfall Method - Argian Dico Alexandra; Nur Fany Al-Farizy; Cyntia Rivatunisa (Jurnal Penelitian Pendidikan IPA, 2023)
The rapid development of the culinary industry demands increased efficiency and effectiveness in information management at Piksi Ganesha Polytechnic. This research aims to design a Culinary Information System using the Waterfall Method to ensure the development of a structured and organized system. The initial stage of research involves analyzing the needs of stakeholders, such as students, lecturers, and administration. This analysis becomes the basis for designing a system that meets user needs and expectations. The design process is carried out in stages, starting from overall system design, database, and user interface, to application business logic. System implementation is carried out after the design is complete, ensuring that each stage has been properly verified and validated. System testing is carried out thoroughly to ensure system quality and reliability. The results of this research indicate that the Waterfall Method provides a solid and structured framework for the development of Culinary Information Systems. Complete documentation, good risk management, and a focus on quality help ensure successful system implementation. Its suitability for stable projects makes it the right choice for the development of a Culinary Information System at Piksi Ganesha Polytechnic. The conclusions of this research contribute to further understanding of the application of the Waterfall Method in the context of information system development in educational institutions.